Analysis of price setting process and pricing decision art object: A case study in art contractor industry - Chrismantya Dwi Satriya Nugroho; Ludira Yudha (Universitas muhammadiyah malang, 2023)
Price setting s a very complex matter and can bring profits and losses to the business if it is wrong in making pricing decisions. Art objects have different standards in determining their prices so that they do not have a definite price standard. This research focuses on how to determine the price of art objects through the pricing process and the value brought by the art objects. This research is a case study research using a qualitative approach. The company studied is an art contractor located in Bali. Researchers conducted field observations, studied company data and conducted interviews. The results of this study show pricing decision-making process in the art contracting industry has several stages to estimate project costs as a basis for making decisions to determine the final price. Each stage of the process correlates with one another and will reveal the costs of the project. The valuation of the art object is added to the project cost based on the artist's skill in making the art object. Each project will have a different value that is tailored to the artist who made the work on the project.